Inschriftenkulturen im kommunalen Italien Traditionen, Brüche, Neuanfänge - Bolle, Katharina; Höh, Marc von der; Jaspert, Nikolas (Materiale Textkulturen, 2019)
The volume examines the epigraphic cultures of Italian communes during the High Middle Ages and their relationship to earlier epigraphic cultures in antiquity and the Early Middle Ages. It focuses especially on the question of continuity and breaks and the influence of the ancient epigraphic heritage on Medieval epigraphic practice in the cities.